DEVELOPMENT OF MIND MAPPING BASED POCKETBOOK AS A LEARNING MEDIA FOR ACCOUNTING SERVICES - Malinda Wartini; Supri Wahyudi Utomo; Elly Astuti (Universitas Negeri Yogyakarta, 2022)
The pocket book is small so it's practical. Students can use it to study anytime and anywhere. The concept of mind mapping presented with colour images can stimulate the brain's performance to make it easier to understand the material. This study aims to develop a mind mapping-based pocket book on accounting materials for service companies. The development model used is the 4D Thiagarajan model, which starts from the definition, design, development, and deployment stages. The validity test of six validators who are experts in their fields shows valid results. The material expert's assessment is in the very good category. The media expert's assessment got a fairly good category, and the linguist's assessment got a very good category. The practicality test involving 20 randomly selected respondents showed practical results. Based on the results of the assessment with predetermined criteria, it can be concluded that a pocket book based on mind mapping in service company accounting materials is said to be suitable for use as a learning medium. Keywords: Development Research; Learning Media; Pocket Book; Mind Mapping; Service Company Accounting